Răspuns :
Răspuns: - x² - 20x + 59
Explicație pas cu pas:
Salutare!
2(x-6)² +(x-2√3)(x+2√3) - (2x-1)² =
2•(x² - 2•x•6 + 36)+[x²-(2√3)²]-(4x² - 4x + 1) =
2x² - 24x + 72 +(x² - 4•3) - 4x² + 4x - 1 =
2x² - 24x + 72 + x² - 12 - 4x² + 4x - 1 =
- x² - 20x + 59
- Am folosit formulele:
(a – b)² = a² – 2ab + b²
a² – b² = (a + b)(a – b)
#copaceibrainly
Raspuns:
-x²-20x+59
Explicatie pas cu pas:
Salutare ! ʕ•ᴥ•ʔ
2(x-6)²+(x-2√3)(x+2√3)-(2x-1)2
2(x²-12x+36)+x²-4×3-(4x²-4x+1)
2x²-24x+72+x²-12-4x²+4x-1
-x²-20x+59
᯾jsksksksk᯾